Exposure assessment and lung function in pig and poultry farmers. Issue 6 (1st June 2001) - Radon, K; Weber, C; Iversen, M; Danuser, B; Pedersen, S; Nowak, D
Abstract : OBJECTIVES: To describe the relation between spirometric findings and farming characteristics and variables of exposure to organic dust measured during work in animal buildings. Farmers have traditionally been described as having one of the most dangerous occupations, so a large scale study on European farmers was carried out. This is the report of the second part of that study. METHODS: 40 pig farmers in Denmark and 36 poultry farmers in Switzerland were chosen randomly and were assessed over 1 working day. RESULTS: Mean (SD) baseline spirometric results in pig farmers were higher than in poultry farmers (forced expiratory volume in 1 second (FEV1 ) (% of reference value) 108.3 (16.7) v 100.2 (14.2); p=0.04). Baseline lung function results were significantly associated with ventilation of the animal houses. Furthermore, temperature was related to spirometric findings in pig farmers. CONCLUSIONS: Ventilation of the animal house and temperature might influence respiratory morbidity in farmers.